Pré-natal: entraves e desafios - GOMES, Lisandra Cristina Barbosa (2020)
This study aims to understand the main obstacles and difficulties faced by pregnant women to initiate and continue prenatal care in a Basic Health Unit (UBS) and to report possible solutions to reduce and/or solve problems that negatively affect their pre-natal care from the perception of pregnant women. This is a descriptive, qualitative approach. Theoreticalmethodological framework presented in the Theory of Foucault (1989) that grounded the discussion on the power relations between institutions, health professionals and users who sought prenatal care. It was held at UBS, located in the Guamá neighborhood, in Belém/PA, linked to the Municipal Secretariat. It involved 15 pregnant women enrolled in prenatal care at this UBS/Guamá; were adopted as primigra- ent inclusion criteria from the 6th month of gestation, which started prenatal late; as exclusion criteria, pregnant women multiparous and/or under 18 years and/or who did not accept to participate in the research. Data collection was done through an individual face-to-face interview, semi-structured with open and closed questions related to the problems encountered by each pregnant woman to initiate and/or continue prenatal care and about measures that can be adopted to reduce or solve them, starting them from the conception of these pregnant women. Data analysis was performed using the Bardin content analysis method. The study complied with the norms and guidelines established in Resolution 466/12 of the National Health Council (CNS) and submitted to the Research Ethics Committee (CEP) - ICS/UFPA for authorization to start the research. Through analysis of the results, it was observed that socioeconomic factors did not significantly influence the discontinuation or postponement of prenatal care, being overcome by the institutional barriers that were the main obstacles to the lack of accessibility in the services and high degree of dissatisfaction of the users with the assistance offered. It was possible to conclude that the questions related to poor service go far beyond the structure of the service. They involve public health policies, service management, and the humanization of professionals to perform good care practices.